Masih Efektifkah City Branding terhadap Peningkatan Jumlah Wisatawan - Gideon Christopher Hamzah (Akubis : Jurnal Akuntansi dan Bisnis, 2021)
Currently, the development of technology andknowledge developed with very fast and unlimited, this makesall forms of information can be easily accessed or in the know.This convenience makes all the people getting interested toknow a variety of new information and also share a variety ofinformation and experience. Similarly happens to the world oftourism, see the greater opportunities that exist to makecompetition in the world tourism is increasingly rapidlydevelops, it can be seen by many different cities who do theactivities of city branding or activities promoting and makingthe city as a tourist destination with a wide range of ways thatprovide a wide range of permissions that facilitate a variety oftourism activities more rapidly evolving improvements, avariety of public facilities and infrastructure, and various otherpromotional way. But in reality not all city branding goes inaccordance with the expectations that existed, in some citytours that the influence of city branding is not running or failed.Yet the number of conceptual research which deals with theeffectiveness of city branding in an increasing number oftourists, as well as to examine theoretically about effectivenesscity branding against an increase in tourists.